Fishing for Foresters: A New Institutional Analysis of Community Participation in an Aboriginal-owned Forest Company - DiFrancesco, Darryn Anne (University of Ottawa (Canada), 2010)
Aboriginal groups across Canada are looking for new ways to improve the living conditions of their people. Coast Tsimshian Resources LP is a forest company that is collectively owned by the Lax Kw'alaams band, a traditional fishing community in northern British Columbia. This research investigates the collectively-owned company as a possible creative means toward development, but in the process uncovers the significance of community 'embeddedness' in shaping development outcomes. Data was collected primarily through semi-structured and informal interviews with respondents from the community and company, among others. Interviews revealed the problem of a disconnection between the community and company. Through a New Institutional Analysis, which pays particular attention to context, the possible reasons for the disconnect are explored, and community 'embeddedness' is presented as a way of understanding it. Fishing is identified as a culturally salient practice and serves as a point of comparison to explain the lack of participation in the company's forestry activities. Suggestions for ways the company can work within this 'embeddedness' to ameliorate the disconnect are provided, and an elevated appreciation of the "sub-institutional elements" within New Institutional theory is suggested. Finally, the community-owned company is evaluated in terms of its ability to meet the development goals and visions of the Lax Kw'alaams band and First Nations in Canada.
Keywords: Geography.; Agriculture, Forestry and Wildlife.; Native American Studies.